A cursory review of the identification strategies - Fabio Gaetano Santeramo (Agricultural and Food Economics, 2015)
The article provides a literature review on the topic of identification of supply and demand. In particular, it discusses the identification problem, that is the issue of having to solve for unique values of the parameters of the structural model from the values of the parameters of the reduced form of the model. We summarize several methodologies employed in the literature to solve this problem and gives practical examples. These solutions include, but are not limited to, using instrumental variables, adopting a recursive structure, holding demand constant, and imposing inequality constraints in order to restrict the domain of estimates. We also discuss on two major recent contributions in agricultural economics. The review will guide researchers in selecting the most suited approach to identify demand and supply.
Keywords: 330; Econometrics; Identification; Supply; Demand